The Conformationally Sensitive Spatial Distance Between the TM3-4 Loop and Transmembrane Segment 7 in the Glutamate Transporter Revealed by Paired-Cysteine Mutagenesis - Qu, Qi; Wang, Ji; Li, Guiping; Chen, Rongqing; Qu, Shaogang (Frontiers in Cell and Developmental Biology, 2021)
Excitatory amino acid transporters can maintain extracellular glutamate concentrations lower than neurotoxic levels by transferring neurotransmitters from the synaptic cleft into surrounding glial cells and neurons. Previous work regarding the crystal structures of GltPh, GltTK, excitatory amino acid transporter 1 (EAAT1), EAAT3 and alanine serine cysteine transporter 2 described the transport mechanism of the glutamate transporter in depth. However, much remains unknown about the role of the loop between transmembrane segment 3 and 4 during transport. To probe the function of this loop in the transport cycle, we engineered a pair of cysteine residues between the TM3−TM4 loop and TM7 in cysteine-less EAAT2. Here, we show that the oxidative cross-linking reagent CuPh inhibits transport activity of the paired mutant L149C/M414C, whereas DTT inhibits the effect of CuPh on transport activity of L149C/M414C. Additionally, we show that the effect of cross-linking in the mutant is due to the formation of the disulfide bond within the molecules of EAAT2. Further, L-glutamate or KCl protect, and D,L-threo-β-benzyloxy-aspartate (TBOA) increases, CuPh-induced inhibition in the L149C/M414 mutant, suggesting that the L149C and M414C cysteines are closer or farther away in the outward- or inward-facing conformations, respectively. Together, our findings provide evidence that the distance between TM3−TM4 loop and TM7 alter when substrates are transported.